Status Objek Perjanjian Pengikatan Jual Beli Lunas Sebagai Harta Pailit Pengembang Berdasarkan Perspektif Keadilan Dan Kepastian Hukum Bagi Pembeli - Tambuwun, Maria Bertha Ismulyani (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
In practice, the Sale and Purchase Agreement is often used by Developers to bind themselves with Buyers prior to signing the Deed of Sale and Purchase. If a developer becomes bankrupt and the Deed of Sale and Purchase has not been signed as a continuation of the Binding Agreement of Sale and Purchase, then the object in the Binding Agreement of Sale and Purchase may enter into the Boedel Bankruptcy Developer, which in reality the object no longer belongs to the developer because it has been paid off and handed over to the Buyer. The writer analyzes and understands that this is not in accordance with the concept of justice and legal certainty. The research method used is normative juridical through an approach to the applicable laws and regulations. Another approach is the conceptual approach which studies the doctrines and views in the law science. In the end, these legal theories provide a strong basis regarding the object of the Binding Agreement of Sale and Purchase Paid that should have been issued from the Boedel Bankruptcy Developer. Keywords: Binding Agreement of Sale and Purchase; Bankruptcy; Buyer